Belize. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Belize during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as public policies, manuals, governance, phytosanitary, resilience against climate change, family farming, technology, safety and food safety. Likewise, the inclusion of field schools, small farmers and human resources administration was supported. Finally, work was done on the sugar value chain.